(untitled) (World Bulletin of Public Health, 2022)
There is an undoubted link between chronic lung diseases in children and adults. This is a single clinical problem for pediatricians and therapists, it has not only medical, but also social significance. Chronic respiratory diseases that began in childhood often lead to disability of patients in adulthood, and sometimes to dramatic outcomes.